Preoperative fibrinogen-to-lymphocyte ratio as a prognostic biomarker for non-muscle-invasive bladder cancer - Zhang, Xueqiao; Su, Shiqiang; Liu, Lizhe; Song, Feifan; Cui, Xiongjie; Cao, Yunpeng; Li, Chao; Li, Shen; He, Hanxing; Kang, Yuanhui; Zhang, Jin (Frontiers in Oncology, 2026)
ObjectiveAlthough the fibrinogen-to-lymphocyte ratio (FLR) is an established prognostic biomarker in various solid tumors, its role in non-muscle-invasive bladder cancer (NMIBC) remains poorly defined. This study aimed not only to investigate the predictive value of preoperative FLR for overall survival (OS) in NMIBC patients undergoing transurethral resection of bladder tumor (TURBt), but also to develop and validate a novel FLR-based nomogram as a practical clinical tool.MethodsThis retrospective study enrolled 304 NMIBC patients who underwent TURBt at the Shijiazhuang People’s Hospital between November 2013 and January 2024, with OS as the primary endpoint. The optimal prognostic cutoff for FLR was determined by maximizing the Youden index via receiver operating characteristic (ROC) curve analysis. Propensity score matching (1:2) was employed to balance baseline confounders. The dose-response relationship between continuous FLR and mortality risk was evaluated using restricted cubic splines (RCS), which confirmed a linear association. Subsequently, independent prognostic factors identified through Cox proportional hazards regression were integrated to construct a nomogram. The model’s predictive accuracy and clinical utility were then comprehensively evaluated using the concordance index (C-index), calibration curves, time-dependent ROC curves, and decision curve analysis (DCA).ResultsThe optimal FLR cutoff was identified as 2.91. Patients in the high-FLR group (FLR ≥ 2.91) exhibited significantly poorer OS (P < 0.001) and cancer-specific survival (CSS; P = 0.004). RCS analysis confirmed a significant positive linear association between increasing FLR levels and all-cause mortality risk. Critically, multivariate Cox regression validated FLR as an independent predictor for both OS (Hazard Ratio (HR): 1.520, 95% Confidence Interval (CI): 1.149-2.010) and CSS (HR: 1.536, 95% CI: 1.033-2.284). Integrating FLR into a baseline model improved the C-index for OS prediction from 0.739 to 0.772. The resulting nomogram demonstrated robust discrimination (C-index: 0.772), excellent calibration, and superior net clinical benefit in DCA.ConclusionPreoperative FLR is an independent predictor of overall survival in NMIBC, characterized by a robust linear dose-response relationship with mortality risk. This cost-effective biomarker, integrated into our validated nomogram, enhances risk stratification to guide personalized postoperative management.